2018
DOI: 10.2337/db17-1207
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA Profiles Associated With Hyperglycemia in Patients With Type 1 Diabetes

Abstract: We investigated plasma microRNA (miRNA) profiles associated with variation of hyperglycemia, measured as hemoglobin A (HbA), in two panels of patients with type 1 diabetes (T1D). Using the HTG Molecular Diagnostics EdgeSeq platform, 2,083 miRNAs were measured in plasma from 71 patients included in a screening panel. Quantitative real-time PCR was used to measure the candidate miRNAs in plasma from 95 patients included in an independent replication panel. We found 10 miRNAs replicated in both panels and 4 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 48 publications
2
54
0
1
Order By: Relevance
“…Satake et al measured plasma levels of 2083 known miRNAs and found that 54 miRNAs correlated with hyperglycemia in patients with T1DM. Furthermore, in this study, three (miR‐193a‐5p, miR‐200c‐3p, and miR‐7‐1‐3p) positively correlated with hemoglobin A1C (HbA1C) levels, whereas three miRNAs (miR‐1228‐3p, miR‐6793‐5p, and miR‐6799‐3p) negatively correlated with HbA1C levels …”
Section: Possible Associated Mechanism Between Mirnas and Dmmentioning
confidence: 49%
“…Satake et al measured plasma levels of 2083 known miRNAs and found that 54 miRNAs correlated with hyperglycemia in patients with T1DM. Furthermore, in this study, three (miR‐193a‐5p, miR‐200c‐3p, and miR‐7‐1‐3p) positively correlated with hemoglobin A1C (HbA1C) levels, whereas three miRNAs (miR‐1228‐3p, miR‐6793‐5p, and miR‐6799‐3p) negatively correlated with HbA1C levels …”
Section: Possible Associated Mechanism Between Mirnas and Dmmentioning
confidence: 49%
“…The above study also corroborates well with our finding that miR-876-3p inhibition leads to decreased expression of pro-inflammatory cytokines in CI-induced IR adipocytes suggesting the role of latter in regulation of inflammatory micromilieu. miR876 has been found to be elevated in type 1 diabetes patient (Satake et al 2018). It has also been showed that miR876-5p is elevated in human trophoblast during gestational diabetes (Bari et al 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Ischemia/reperfusion-induced cardiac injury [76], cardiac cachexia, heart failure [77], atrial fibrillation [78], diffuse myocardial fibrosis in hypertrophic cardiomyopathy [30], coronary artery disease [79], pulmonary arterial hypertension [74], gestational diabetes mellitus [80], diabetes mellitus [13,23,81,82] [83] Hypertension [84], hypoxia-induced pulmonary hypertension [85], myocardial ischemia/reperfusion injury, acute myocardial infarction [84], ischemic dilated cardiomyopathy [66], obesity, regulation of insulin sensitivity [86], T1DM [87] hsa-miR-125b-5p 11q24.1 21q21.1 [88] Acute ischemic stroke [89], acute myocardial infarction [90,91], ischemic dilated cardiomyopathy [66], ascending aortic aneurysm [49], gestational diabetes mellitus [92], T1DM [93,94], T2DM [95] hsa-miR-126-3p 9q34.3 [96] Acute myocardial infarction [72], T2DM [53,97], T2DM with major cardiovascular events [53], gestational diabetes mellitus [98] hsa-miR-130b-3p 22q11.21 Hypertriglyceridemia [99,100], intracranial aneurysms [101], hyperacute cerebral infarction [102], T2DM [52,103,104], gestationa...…”
Section: Introductionmentioning
confidence: 99%